Population dynamics of Ectatomma brunneum (Hymenoptera, Formicidae) under laboratory conditions - Tofolo, Viviane Cristina [UNESP]; Giannotti, Edilberto [UNESP] (My University, 2005)
Ectatomma brunneum Smith is an ant of wide distribution in Latin America, occurring from Panama to Argentina, and it can be found all over Brazil, usually in areas with open vegetation such as forest edges or clearings, but also in crops, pastures and secondary vegetation. The population dynamics of insects has been studied by means of detailed description of the population mortality, using ecological life tables and specific age. After gathering the daily data, the life table and entropy were calculated; the value obtained for life expectancy was ex = 642.008 days, somewhat similar to the mean longevity for these ants (594.55 days). The value for entropy was H=0.513 (between 0.5 and 1.0), indicating few deaths of young individuals (first death on the 70 th day) and making the survival curve of this species show a relatively convex aspect, with a gradual decrease as days went by.
Keywords: Ectatomma brunneum; Entropy; Life expectancy; Mean longevity; Ponerinae; Formicidae; Hexapoda; Hymenoptera; Insecta